Site-Specific N-Glycan Characterization of Grass Carp Serum IgM - Su, Yi-Ling; Wang, Bing; Hu, Meng-Die; Cui, Zheng-Wei; Wan, Jian; Bai, Hao; Yang, Qian; Cui, Yan-Fang; Wan, Cui-Hong; Xiong, Li; Zhang, Yong-An; Geng, Hui (Frontiers in Immunology, 2018)
Immunoglobulin M (IgM) is the most abundant antibody in teleost fish and plays a crucial role in humoral adaptive immunity. The N-linked carbohydrates presenting on IgM have been well documented in higher vertebrates, but little is known regarding site-specific N-glycan characteristics in teleost IgM. In order to characterize these site-specific N-glycans, we conducted the first study of the N-glycans of each glycosylation site of the grass carp serum IgM. Among the four glycosylation sites, the Asn-262, Asn-303, and Asn-426 residues were efficiently glycosylated, while Asn-565 at the C-terminal tailpiece was incompletely occupied. A striking decrease in the level of occupancy at the Asn-565 glycosite was observed in dimeric IgM compared to that in monomeric IgM, and no glycan occupancy of Asn-565 was observed in tetrameric IgM. Glycopeptide analysis with liquid chromatography-electrospray ionization tandem mass spectrometry revealed mainly complex-type glycans with substantial heterogeneity, with neutral; monosialyl-, disialyl- and trisialylated; and fucosyl-and non-fucosyl-oligosaccharides conjugated to grass carp serum IgM. Glycan variation at a single site was greatest at the Asn-262 glycosite. Unlike IgMs in other species, only traces of complex-type and no high-mannose glycans were found at the Asn-565 glycosite. Matrix-assisted laser desorption ionization-time of flight mass spectrometry of released glycans confirmed that the overwhelming majority of carbohydrates were of the complex-type. These results indicate that grass carp serum IgM exhibits unique N-glycan features and highly processed oligosaccharides attached to individual glycosites.